Revealing the Electrophysiological Correlates of Working Memory-Load Effects in Symmetry Span Task With HHT Method - Chuang, Kai-Yu; Chen, Yi-Hsiu; Balachandran, Prasad; Liang, Wei-Kuang; Juan, Chi-Hung (Frontiers in Psychology, 2019)
Complex span task is one of the commonly used cognitive tasks to evaluate an individual’s Working Memory Capacity (WMC). It is a dual task consisting of a distractor subtask and a memory subtask. Though multiple studies have utilized complex span tasks, the electrophysiological correlates underlying the encoding and retrieval processes in working memory span task remain uninvestigated. One previous study that assessed Electroencephalographic (EEG) measures utilizing complex span task found no significant difference between its working memory loads, a typical index observed in other working memory tasks (e.g. n-back task and digital span task). The following design constructs of the paradigm might have been the reason. (1) The fixed-time limit of the distractor subtask may have hindered the assessment of individual WMC precisely. (2) Employing a linear-system-favoring EEG data analysis method for a nonlinear system such as the human brain. The current study utilizes a Symmetry span task sequential to a distractor subtask. At the afore mentioned bounds, the distractor subtask was equipped with a varying time-limit across individual subjects which could provide a precise measure of individual WMC. This study investigates if the complex span task resonates EEG patterns similar to the other working memory tasks in terms of working memory-load by utilizing Ensemble Empirical Mode Decomposition (EEMD) of Hilbert-Huang Transform (HHT). Prior expectations were to observe a decrement in the P300 component of Event-Related Mode (ERM) and a decrement in the power of alpha and beta band frequency with increasing working memory-load. We observed a significantly higher P300 amplitude for the low load condition compared to the high load condition over the circumscribed brain network across F4 and C4 electrodes. Time-frequency analysis revealed a significant difference between the high and low load conditions at alpha and beta band over the frontal, central, and parietal channels. The results from our study demonstrate precise differences in EEG data pertaining to varied memory-load differences in the complex span task. Thus, assessing complex span tasks with the HHT-based analysis may aid in achieving a better signal to noise ratio and effect size for the results in working memory EEG studies.